The effect of perioperative allergic conjunctivitis on corneal lymphangiogenesis after corneal transplantation. Issue 10 (7th June 2011) - Flynn, T H; Ohbayashi, M; Dawson, M; Larkin, D F P; Ono, S J
Abstract : Introduction: Perioperative allergic conjunctivitis accelerates the speed of corneal allograft rejection. This study examines the effect of allergic conjunctivitis, with and without dexamethasone treatment, on the early inflammatory response and lymphangiogenesis in the host cornea following corneal transplantation. Methods: Allogeneic fully MHC-mismatched C57Bl/6 strain donor corneas were transplanted into naive A/J mice and into A/J mice with active allergic conjunctivitis. Further groups of allograft recipients with allergic conjunctivitis were treated post-operatively with twice daily topical dexamethasone 0.1% or phosphate-buffered saline. Mice were killed on days 2 and 6 and corneas were examined by (i) fluorescent immunohistochemistry of frozen sections using anti-CD11b, anti-F4/80 and anti-Gr-1 antibodies, or (ii) whole-mount staining with anti-LYVE-1 antibody. Lymphatic ingrowth and numbers of cells infiltrating the host cornea were compared between groups. Results: There were significantly higher numbers of CD11b + cells and LYVE-1 + vessels in the host cornea at day 2 in allergic compared with naive recipients, but no differences between naive and allergic recipients at day 6. In allergic eyes, dexamethasone treatment significantly inhibited LYVE-1 expression at days 2 and 6, and significantly improved allograft survival in recipients with allergic conjunctivitis if maintained for a week. Conclusions: The innate immune response to allogeneic corneal tissue is more vigorous in the presence of allergic conjunctivitis than in naive eyes and is associated with accelerated lymphatic ingrowth to host cornea. Topical dexamethasone inhibits lymphatic ingrowth and this may be one mechanism by which topical steroid enhances graft survival.